Supramolecular photochemistry : controlling photochemical processes - Ramamurthy, V.; Inoue, Yoshihisa, 1949- (Hoboken, NJ : Wiley, 2011)
'This is the most updated, comprehensive collection of monographs on all aspects of photochemistry and photophysics related to natural and synthetic, inorganic, organic, and biological supramolecular systems. Supramolecular Photochemistry: Controlling Photochemical Processes addresses reactions in crystals, organized assemblies, monolayers, zeolites, clays, silica, micelles, polymers, dendrimers, organic hosts, supramolecular structures, organic glass, proteins and DNA, and applications of photosystems in confined media. This landmark publication describes the past, present, and future of this growing interdisciplinary area.'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Photochemistry; Supramolecular chemistry